2020
DOI: 10.3390/sports8010009
|View full text |Cite
|
Sign up to set email alerts
|

The Weather Impact on Physical Activity of 6–12 Year Old Children: A Clustered Study of the Health Oriented Pedagogical Project (HOPP)

Abstract: It is commonly known that children do not engage in a sufficient amount of physical activity. Weather conditions and day length may influence physical activity of children. Little is known about the relationship between physical activity and seasons. The purpose of this study was to investigate the relationships between weather conditions and physical activity in 6–12 year old children based on hip-worn Actigraph wGT3X–BT accelerometer data. The study sample consisted of 2015 subjects aged 6–12 years from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Consistent with previous research that there was no significant correlation between temperature and SB among our survey participants [ 53 , 54 , 55 , 56 , 57 , 58 ], a study on a sample of 740 Hong Kong adolescents reported that there was no significant relationship between temperature and SB during weekdays [ 57 ]. Another study from 722 children aged 10–12 years in five countries found that temperature was not significantly associated with SB [ 58 ].…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous research that there was no significant correlation between temperature and SB among our survey participants [ 53 , 54 , 55 , 56 , 57 , 58 ], a study on a sample of 740 Hong Kong adolescents reported that there was no significant relationship between temperature and SB during weekdays [ 57 ]. Another study from 722 children aged 10–12 years in five countries found that temperature was not significantly associated with SB [ 58 ].…”
Section: Discussionsupporting
confidence: 91%
“…As mentioned above, the study in the United States found an effect of season on time outdoors; however, physical activity was not significantly different between seasons [29]. On the other hand, children in Norway [60,61], Portugal [62], and England [63] were more active in warmer, drier seasons, and children in Australia were more active in winter than summer [64,65]. Interestingly, in the latter study, boys did not exhibit seasonal fluctuation in physical activity [64].…”
Section: Limitationsmentioning
confidence: 64%
“…As expected, boys outperformed girls in five fitness tests assessing cardiorespiratory endurance, coordination, speed, and muscle power. The better performance of boys in these tests is likely related to differences in body composition 66 , 67 , endocrine levels 68 , and activity levels 20 , 55 , 69 , 70 . Pre-adolescent boys tend to exhibit lower fat and higher lean mass than pre-adolescent girls 66 , 67 .…”
Section: Discussionmentioning
confidence: 99%